Alteration of basaltic glass within the Surtsey hydrothermal system, Iceland – Implication to oceanic crust seawater interaction - Prause, Simon; Weisenberger, Tobias B.; Kleine, Barbara I.; Monien, Patrick; Rispoli, Concetta; Stefánsson, Andri (Journal of Volcanology and Geothermal Research, 2022)
Low-temperature hydrothermal alteration of basaltic glass on the seafloor has important implications on the chemical evolution of the oceanic crust and seawater composition. However, mass fluxes resulting from seawater-glass interaction in this type of environment remain poorly understood. This study presents new results on element mobilities for the palagonitization of basaltic glass and bulk rock hydrothermal alteration at Surtsey volcano, Iceland over a time period of 50-years. Assessments of element mobilities were based on 1) immobile trace element isocon mass balance for palagonitization, 2) the assumption of large scale TiO2 immobility during bulk rock alteration and 3) chemical analyses of pore fluids and authigenic minerals. Element mobilities of glass alteration vary between initial palagonitization and subsequent palagonite maturation: Initially, palagonitization of sideromelane leaches SiO2, Al2O3, MgO, CaO, Na2O, K2O from the glass. Following this, the maturation of the palagonitized glass causes re-uptake of all of the abovementioned elements except for CaO, which shows either no change or slight uptake, and Na2O, which continues to be lost from the palagonitized glass. Among major elements TiO2 and FeO can be considered immobile during palagonitization, but not during the subsequent aging process of palagonitized glass. Among trace elements Hf, Ta, Zr, Nb, Y and REE were found to be immobile at all stages of the alteration. On the bulk rock scale, comprising both glass alteration and the formation of authigenic phases, early-stage alteration at Surtsey releases SiO2, Al, Mg and Ca to the fluid, whereas late-stage alteration poses a sink of SiO2, Al, Mg, Ca and Na. Net element budgets during early- and late-stage alteration indicate that chemical exchange between basaltic tuffs and seawater derived fluids at Surtsey acts as a long-term source of dissolved Ca, Al and SiO2 for seawater as well as a long-term sink for seawater Mg and Na.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Hydrothermal alteration; ICDP; Mass balance; Palagonitization; Surtsey volcano; SUSTAIN